Project of a beamline for the NESTOR storage ring linac to provide nuclear physics research - Mytrochenko, V.V.; Perezhogin, S.O.; Kushnir, V.A.; Ganenko, V.B.; Ayzatsky, M.I.; Kovalenko, G.D. (Вопросы атомной науки и техники, 2021)
The results of selfconsistent beam dynamics simulation are presented for the linac of the NESTOR storage ring. Consideration is given to the influence of particle energy change at the output of the electron gun during the current pulse. The obtained data have formed the basis for the computation of the beam transport line for research in the field of high energy physics. Представлено результати моделювання самоузгодженої динаміки пучка в прискорювачі накопичувального кільця НЕСТОР з урахуванням впливу зміни енергії частинок на виході електронної гармати під час імпульсу струму. Отримані дані лягли в основу розрахунку лінії транспортування пучка для забезпечення досліджень у галузі фізики високих енергій. Представлены результаты моделирования динамики самосогласованного пучка в линейном ускорителе накопителя НЕСТОР с учетом влияния изменения энергии частиц на выходе электронной пушки во время импульса тока. Полученные данные легли в основу расчета линии транспортировки пучка для исследований в области физики высоких энергий.